Bert Sheedy and Marj Sheedy oral history collection - Sheedy, P. B. (Philip Bert); Sheedy, Marj. (1964)
A collection of interviews collected by Bert and Marj Sheedy concerning the history of the Canberra district and its people.
Recording media varies.
Interviews conducted by Bert Sheedy.
Transcripts not available.
Recorded from 1964 to 1985.
Digital master available
Keywords: Canberra Region (A.C.T.) -- History